Glass formers display universal non-equilibrium dynamics on the level of single-particle jumps - Helfferich, Julian; Vollmayr-Lee, K.; Ziebert, Falko; Meyer, H.; Baschnagel, Jörg (epl, 2015)
Glasses are inherently out-of-equilibrium systems evolving slowly toward their equilibrium state in a process called physical aging. During aging, dynamic observables depend on the history of the system, hampering comparative studies of dynamics in different glass formers. Here, we demonstrate how glass formers can be directly compared on the level of single-particle jumps, i.e. the structural relaxation events underlying the α-process. Describing the dynamics in terms of a continuous-time random walk, an analytic prediction for the jump rate is derived. The result is subsequently compared to molecular-dynamics simulations of amorphous silica and a polymer melt as two generic representatives of strong and fragile glass formers, and good agreement is found.
Gesehen am 27.09.2022